RESEPSI MASKULINITAS PEREMPUAN DI FILM RAYA AND THE LAST DRAGON - Nurul Aini, Riska; Adiyanto, Wiwid (Ilmu Komunikasi, FISIP Universitas Pasundan, 2025)
Earlier Disney films tended to portray women as weak or cunning. Disney has also been criticized for its depiction of mental health in the animation. Raya and The Last Dragon is the latest film from Walt Disney Animation Studios with an action adventure genre released on March 3, 2021. Raya and The Last Dragon is the first film that focuses on Southeast Asian culture. This study aims to describe audience reception related to female masculinity in the film Raya and the Last Dragon. This research refers to the interpretive paradigm. This study places the reception method proposed by Stuart Hall as a guide for analysis. The results of this study indicate that audience reception tends to lead to a dominant hegemonic position. The masculinity of women shown in the film Raya and The Last Dragon is shown with courage, strength, skill in playing weapons, good at fighting and hairstyles or appearances that are considered masculine (tomboy), leader and optimistic.